Zmiana społeczna, kapitał społeczny a żywiołowość w logice przejawianego rozumu - Radziewicz-Winnicki, Andrzej (Horyzonty Wychowania, 2009)
The article is devoted to the role of social capital in the development and perception of modern changes, technologies, values, norms etc., in the period of social change in Poland during the last twenty years. In fact, the author presents the comparison between traditional and modern societies. The si tuation in Poland leads to the discovery of unexpected changes, contradictions and paradoxes implemented in the post-communist society. A lot of questions are addressed to the representatives of social sciences. Paradoxically, in the post-industrial era of informationalism and the society of knowledge – in the case of Poland – science and modernity are not conducive to the expected autonomy of new type changes and social relations in modern civil society. What influenced author’s personal views was an invitation to write a paper to this issue of „The Horizons of Education” devoted to, among other things, the human mind, rationality and pragmatism as the impact of new information technologies on the functioning of the contemporary postindustrial society. On the basis of the issue raised, the author confronts the alreadyreached achievements in the field in Poland, arguing that traditional communities, in the contrast to modern structures, limit mass social participation in terms of approval of patterns, norms and values propagated, among others, in the culture of digital modernity represented mostly by the Internet and real democracy. The author makes an attempt to draw the reader’s attention to the native situation within the scope discussed here, which is marked by numerous contradictions of social incompetence.